A Study of the Relationship of Physical Environment to Third Place in Central Festival Hat Yai Shopping Center, Songkhla Province - Phetburi , Wanwisa; ChodChuang, Siripat (Business Administration and Management Journal Review, 2021)
In the current market situation, shopping centers have enhanced their experience of providing services to consumers as a third-place. Which is the place that serve as an alternative to home and work. Because the shopping center has an environment and service, both shops and facilities that meet the needs of consumers fully. This research was aims to (1) study the physical environment affecting the third-place concept and (2) to confirm that the third-place affecting the intention to visit the Central Festival Hadyai shopping center. The sample group is 400 consumers who visit the Central Festival Hat Yai shopping center. Which this research is quantitative research. The method of data collection is questionnaires by using convenient sampling methods from 400 sets of samples. The statistics data analyses were the percentage, mean, and multiple regression analysis. The results showed that the physical environment in its location ( =0.338) and the tenant shop ( =0.456) affect towards on the third-place with statistical significance at 0.05. While the third-place also affecting the intention to visit the shopping center with statistical significance at 0.05.